(untitled) (Communication & Society, 2023)
This article aims to build a better understanding of today’s communicative changes of public diplomacy in the post-truth era. Today, our communication environment has changed compared to decades ago: about 5 billion people communicate online and compete among themselves through their social media narratives, which are the main platform for the distribution of fake news in the post-truth era. The question posed here is: what are the winning narratives in the complex global environment of public diplomacy? Through problematizing review, this article analyses the sources of soft power which were described at the end of the Cold War, and which remain effective even in today’s communication environment. Also, the purpose and influence of public diplomacy has been problematized, analysing how to influence foreign government by influencing its citizens. The paper concludes that the values of soft power described three decades ago only have limited and specific effects on non-European publics, but not on European ones. Additionally, it is impossible to influence European governments by influencing their publics through public diplomacy because the context has changed and the values of soft power in these countries no longer have the former distinctive gap between them.